Posh talk : language and identity in higher education - Preece, Siân, 1960- (Basingstoke [U.K.] ; New York : Palgrave Macmillan, 2009)
"This is an in-depth study of a group of multilingual students from widening participation backgrounds on a first-year undergraduate academic writing program. The book explores ways in which identity positions emerge in the spoken interaction, with a particular focus on gender"--Provided by publisher.
Machine generated contents note: Widening Participation --Theorising and analyzing Identity -- Approaches to Academic Writing -- Multilingual masculinities in the classroom -- Multilingual femininities in the classroom multilingual masculinities in lecturer -- Student interactions -- Multilingual femininities in lecturer -- Student interactions towards inclusion.
Includes bibliographical references (p.196-208) and index.
00025536
Keywords: English language -- Rhetoric -- Study and teaching (Higher); Report writing -- Study and teaching (Higher); Listening -- Study and teaching (Higher); Minorities -- Education (Higher); Women -- Education (Higher); Multicultural education; Feminism and education; Interdisciplinary approach in education